Fun with algorithms 6th International Conference, FUN 2012, Venice, Italy, June 4-6, 2012. Proceedings - Krizanc, Danny; Luccio, Flaminia; Kranakis, Evangelos (Lecture Notes in Computer Science,, 2012)
This book constitutes the refereed proceedings of the 6th International Conference, FUN 2012, held in June 2012 in Venice, Italy. The 34 revised full papers were carefully reviewed and selected from 56 submissions. They feature a large variety of topics in the field of the use, design, and analysis of algorithms and data structures, focusing on results that provide amusing, witty but nonetheless original and scientifically profound contributions to the area.